Pengaruh Penggunaan Media Audiovisual Terhadap Kemampuan Memahami Puisi Pada Siswa Kelas XI 2 MAN 1 Pati Tahun 2023 - Nabila Aurora Putri Pradewi; Ngatmini Ngatmini; Agus Wismanto (Institut Nalanda, 2023)
This research aims to determine the effect of using audio-visual media on the ability to understand poetry in class XI 2 MAN 01 PATI students in 2023. The approach taken in this research is a quantitative approach with a pre-experimental design, with a pre-test-post-test control group design design. The population in this study were students of class XI 2 MAN 01 PATI. The sample in this study consisted of 30 students. The technique used is a test to complete 20 multiple choice questions. The average score obtained on the student learning outcomes test before using audiovisual media was 66.67. Meanwhile, after using audio-visual media the average test score was 92.33. Calculation of data from the pre-test and post-test was carried out using SPSS 26. Based on the results of the paired sample t-test calculation, the data obtained a sig value. (2-tailed) of 0.000. Thus, it means 0.000 < 0.05. There is a significant difference between the pre-test and post-test scores. The comparison results between the t-test and t-table values ​​also show that the t-test values ​​are higher than the t-table values. It can be seen that the t-test value is 13.205, and the t-table value is 1.699. This means 13.205 > 1.699. It can be interpreted that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. From this explanation, it means that there is a significant influence on student grades before and after learning using audio-visual media.